Human Heterozygous ENPP1 Deficiency Is Associated With Early Onset Osteoporosis, a Phenotype Recapitulated in a Mouse Model of Enpp1 Deficiency. (5th December 2019) - Oheim, Ralf; Zimmerman, Kristin; Maulding, Nathan D; Stürznickel, Julian; von Kroge, Simon; Kavanagh, Dillon; Stabach, Paul R; Kornak, Uwe; Tommasini, Steven M; Horowitz, Mark C; Amling, Michael; Thompson, David; et al.
ABSTRACT: Biallelic ENPP1 deficiency in humans induces generalized arterial calcification of infancy (GACI) and/or autosomal recessive hypophosphatemic rickets type 2 (ARHR2). The latter is characterized by markedly increased circulating FGF23 levels and renal phosphate wasting, but aberrant skeletal manifestations associated with heterozygous ENPP1 deficiency are unknown. Here, we report three adult men with early onset osteoporosis who presented with fractures in the thoracic spine and/or left radius, mildly elevated circulating FGF23, and hypophosphatemia. Total hip bone mineral density scans demonstrated osteoporosis ( Z ‐score < −2.5) and HRpQCT demonstrated microarchitectural defects in trabecular and cortical bone. Next‐generation sequencing revealed heterozygous loss‐of‐function mutations in ENPP1 previously observed as biallelic mutations in infants with GACI. In addition, we present bone mass and structure data as well as plasma pyrophosphate (PPi) data of two siblings suffering from ARHR2 in comparison to their heterozygous and wild‐type family members indicative of an ENPP1 gene dose effect. The skeletal phenotype in murine Enpp1 deficiency yielded nearly identical findings. Ten‐week‐old male Enpp1 asj/asj mice exhibited mild elevations in plasma FGF23 and hypophosphatemia, and micro‐CT analysis revealed microarchitectural defects in trabecular and cortical bone of similar magnitude to HRpQCT defects observed in humans. Histomorphometry revealed mild osteomalacia and osteopenia at both 10 and 23 weeks. The biomechanical relevance of these findings was demonstrated by increased bone fragility and ductility in Enpp1 asj/asj mice. In summary, ENPP1 exerts a gene dose effect such that humans with heterozygous ENPP1 deficiency exhibit intermediate levels of plasma analytes associated with bone mineralization disturbance resulting in early onset osteoporosis. © 2019 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.